2005
DOI: 10.1590/s1517-83822005000400004
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation of arbuscular mycorrhizal fungi using Tris-CHl buffer in addition to nutrient solutions

Abstract: The production of inoculum is one of the hindrances in the large scale application of arbuscular mycorrhizal fungi (AMF). The objective of this work was to evaluate the effect of nutrient solutions with or without TrisHCl buffer, on sporulation of AMF. The experiment was carried out in a greenhouse, using a substrate with sand and vermiculite (1:1 v/v). Fifty spores of Gigaspora margarita, Scutellospora heterogama, and Glomus etunicatum were inoculated in Sorghum vulgare (sorghum) or Panicum miliaceum (fodder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
3
11
0
1
Order By: Relevance
“…Hyphal length (5–11 m cm −3 substrate) was similar to values observed by Neumann et al (2009) in a comparable substrate (3.5–8.5 m cm −3 substrate) and was also within the range obtained by Drew et al (2006) in a sand substrate. Spore density was up to five times higher than values reported for pot cultures using a 1:1 sand/vermiculite substrate (up to 200 spores cm −3 substrate) (Silva et al 2005) and ten times the values reported from field samples (up to 100 spores cm −3 substrate) (Oehl et al 2005), but within the range reported by Neumann et al (2009). In the present study, ERM growth in the FC was clearly decreased by the supply of NH 4 + to the pot substrate.…”
Section: Discussionsupporting
confidence: 67%
“…Hyphal length (5–11 m cm −3 substrate) was similar to values observed by Neumann et al (2009) in a comparable substrate (3.5–8.5 m cm −3 substrate) and was also within the range obtained by Drew et al (2006) in a sand substrate. Spore density was up to five times higher than values reported for pot cultures using a 1:1 sand/vermiculite substrate (up to 200 spores cm −3 substrate) (Silva et al 2005) and ten times the values reported from field samples (up to 100 spores cm −3 substrate) (Oehl et al 2005), but within the range reported by Neumann et al (2009). In the present study, ERM growth in the FC was clearly decreased by the supply of NH 4 + to the pot substrate.…”
Section: Discussionsupporting
confidence: 67%
“…etunicatum was shown to produce a high number of spores/g of soil, ranging from 18.6 to 152.8 , in symbiosis with Panicum miliaceum, whereas lower values (from 0.22 to 1.54 spores/g of soil), comparable to spore densities reported by this work, were observed in symbiosis with Sorghum vulgare (Silva et al, 2005).…”
Section: Greenhouse Experimentssupporting
confidence: 76%
“…[41-43, 8, 44, 45]. Addition of organic residues to the substrate is known to increase AM fungal sporulation hence leading to increased inoculum production [46][47][48][49]. Douds et al [8] successfully produced AM fungal inoculum in compost mixed with vermiculite, perlite, or horticultural potting media and observed that the propagule numbers were maximum in vermiculite based media.…”
Section: Effect Of Different Carrier Treatments On Re-inoculation/colmentioning
confidence: 99%